Does Iso-mechanical Power Lead to Iso-lung Damage?: An Experimental Study in a Porcine Model. (May 2020) - Vassalli, Francesco; Pasticci, Iacopo; Romitti, Federica; Duscio, Eleonora; Aßmann, David Jerome; Grünhagen, Hannah; Vasques, Francesco; Bonifazi, Matteo; Busana, Mattia; Macrì, Matteo Maria; Giosa, Lorenzo; Reupke, Verena; et al.
Abstract : Background: Excessive tidal volume, respiratory rate, and positive end-expiratory pressure (PEEP) are all potential causes of ventilator-induced lung injury, and all contribute to a single variable: the mechanical power. The authors aimed to determine whether high tidal volume or high respiratory rate or high PEEP at iso-mechanical power produce similar or different ventilator-induced lung injury. Methods: Three ventilatory strategies—high tidal volume (twice baseline functional residual capacity), high respiratory rate (40 bpm), and high PEEP (25 cm H2 O)—were each applied at two levels of mechanical power (15 and 30 J/min) for 48 h in six groups of seven healthy female piglets (weight: 24.2 ± 2.0 kg, mean ± SD). Results: At iso-mechanical power, the high tidal volume groups immediately and sharply increased plateau, driving pressure, stress, and strain, which all further deteriorated with time. In high respiratory rate groups, they changed minimally at the beginning, but steadily increased during the 48 h. In contrast, after a sudden huge increase, they decreased with time in the high PEEP groups. End-experiment specific lung elastance was 6.5 ± 1.7 cm H2 O in high tidal volume groups, 10.1 ± 3.9 cm H2 O in high respiratory rate groups, and 4.5 ± 0.9 cm H2 O in high PEEP groups. Functional residual capacity decreased and extravascular lung water increased similarly in these three categories. Lung weight, wet-to-dry ratio, and histologic scores were similar, regardless of ventilatory strategies and power levels. However, the alveolar edema score was higher in the low power groups. High PEEP had the greatest impact on hemodynamics, leading to increased need for fluids. Adverse events (early mortality and pneumothorax) also occurred more frequently in the high PEEP groups. Conclusions: Different ventilatory strategies, delivered at iso-power, led to similar anatomical lung injury. The different systemic consequences of high PEEP underline that ventilator-induced lung injury must be evaluated in the context of the whole body. Abstract : The authors studied 42 healthy sedated pigs ventilated in the prone position for 48 h, controlling anesthetic level, hemodynamics, and temperature. Three ventilatory strategies (high tidal volume, high respiratory rate, or high positive end-expiratory pressure [PEEP]) were studied at two levels of mechanical power (15 or 30 J/min, regulated by manipulating the other component variables). Measurements included hemodynamics, lung mechanics, gas exchange, lung histology, and lung weight. High PEEP, as expected, had the greatest adverse hemodynamic impact. For all strategies, similar degrees of histologic lung injury and extravascular lung water accumulation occurred by 48 h, despite different time courses. Paradoxically, a greater degree of alveolar edema occurred at lower mechanical power, perhaps explained by different hemodynamic patterns that favored or reduced extravascular fluid accumulation. These data suggest that over time, the integrated effects resulting from high tidal volume, high respiratory rate, or high PEEP are more important than the direct and immediate consequence of any one of them alone. Ventilator-induced lung injury should be considered holistically in the context of whole-body physiology rather than as an isolated effect on the lung alone.Supplemental Digital Content is available in the text.